Physical Violence in The Educational Process Through The Perspective of Fiqh - Nur Wahyudi; Syarof Nursyah Ismail; Haris Nursyah Arifin (Al-Hayat: Journal of Islamic Education, 2018)
The teacher is a very decisive figure in the learning process of a student. Competent teachers can impart knowledge to their students, both religious and worldly knowledge. However, sometimes teachers who are expected to educate with patience and compassion can turn into 'monsters' at school. Physical violence against students often occurs in the middle of the learning process. The Indonesian government has been very good at responding to this. There are so many laws that protect the rights of students from physical violence in the education process. But what about from a Fiqh perspective? To what extent is the authority of a teacher in sanctioning students from a Fiqh perspective? and What is the Fiqh attitude of a student or student guardian when he is sanctioned by his teacher? Through an in-depth literature method, it was finally concluded that Fiqh also discussed the issue of physical sanctions on students. In this case, Fiqh allows it under certain conditions. These strict conditions must then be met when a teacher will impose physical sanctions on his students. Thus, the basis of Fiqh which is a manifestation of Islamic laws must also be used as a reference in solving the problem of physical sanctions on students in the teaching and learning process.